Use of Industry 4.0 technologies to reduce and valorize seafood waste and by-products: a narrative review on current knowledge - Hassoun, Abdo; Cropotova, Janna; Trollman, Hana; Jagtap, Sandeep; Garcia-Garcia, Guillermo; Parra-López, Carlos; Nirmal, Nilesh; Özogul, Faith; Bhat, Zuhaib; Aït-Kaddour, Abderrahmane; Bono, Gioacchino (Elsevier, 2023)
Fish and other seafood products represent a valuable source of many nutrients and micronutrients for the human diet and contribute significantly to global food security. However, considerable amounts of seafood waste and by-products are generated along the seafood value and supply chain, from the sea to the consumer table, causing severe environmental damage and significant economic loss. Therefore, innovative solutions and alternative approaches are urgently needed to ensure a better management of seafood discards and mitigate their economic and environmental burdens. The use of emerging technologies, including the fourth industrial revolution (Industry 4.0) innovations (such as Artificial Intelligence, Big Data, smart sensors, and the Internet of Things, and other advanced technologies) to reduce and valorize seafood waste and by-products could be a promising strategy to enhance blue economy and food sustainability around the globe. This narrative review focuses on the issues and risks associated with the underutilization of waste and by-products resulting from fisheries and other seafood industries. Particularly, recent technological advances and digital tools being harnessed for the prevention and valorization of these natural invaluable resources are highlighted.
Keywords: Seafood processing by-product; Fish side stream; Fourth industrial revolution; Artificial intelligence; Big data; Smart sensors; Internet of things; Sustainability; Valorization; Innovative technologies; Circular economy